Kewenangan Organ Negara Dalam Penyelenggaraan Pemerintahan - Hakim, Lukman (Jurnal Konstitusi, 2011)
A state is a community organization intended to put the collective life in order. In order to reach such a life, government rules are created as a means of implementing the state duties, and  of  distributing duties and of delimiting powers/ The government or state  administration is a abstraction which is personified and raised by the law as the reality of the law. As an abstraction, the government cannot do any actions without via its organs. It is important for the government to drive the cycle of “power”  and “authority”. In the administrative and constitutional law the terms ‘power’ and “authority’ is closely related to the implementation of the government functions.  Modern states tend to make the duties of government more technical which is more difficult to predict, and as a result it is impossible for laws to provide with legality to all government affairs.